Etnomethodological Study: Revealing Cheating and Whistleblowing Practices at KH School - Adinda Dwi Handayani; Nursanita Nursanita (Lembaga Penelitian Universitas YARSI, 2027)
Fraud in school financial management remains a serious concern due to weak budgeting systems and limited internal controls. This study aims to identify potential fraud in budget management at KH Schools and formulate a whistleblowing system (WBS) as a preventive measure. A qualitative method with an ethnomethodological approach was employed. Primary data were collected through in-depth interviews with foundation leaders, school principals, finance staff, and accounting staff, while secondary data comprised financial reports, budget recapitulations, and budget utilization evaluations. Data validity was assessed through source and technique triangulation. The findings reveal substantial gaps between budgeted and actual expenditures during 2022–2024, alongside relatively long average implementation periods of 94 days in 2022, 112 days in 2023, and 67 days in 2024, indicating inefficiency and potential opportunities for fraud. Based on the Fraud Triangle (Cressey, 1953), opportunity was the dominant factor, driven by the absence of SOPs, weak supervision, and undocumented cross-subsidy practices. The study concludes that KH Schools should strengthen COSO 2013-based internal controls and implement a WBS featuring anonymous reporting, whistleblower protection, and clear follow-up mechanisms to enhance financial accountability.